Health status deterioration in field-protective forest belts in northeastern Bulgaria - Margarita Georgieva; Georgi Georgiev; Plamen Mirchev; Veselin Ivanov; Mihaela Hristova; Sevdalin Belilov; Yonko Dodev; Svetozar Madzhov; Lyubomira Georgieva (Silva Balcanica)
A system of field-protective forest belts was created in the 1950-60s in northeastern Bulgaria to maintain soil moisture, reduce wind speed and protect soil against wind erosion, improve the microclimate, and increase the fertility of agricultural lands. The deciduous tree species such as Fraxinus excelsior, F. angustifolia, F. americana, Gleditsia triacanthos, Quercus robur, Q. cerris, Q. rubra, Robinia pseudoacacia, Ulmus minor etc., were in common use for afforestation. Since 2020, the processes of deterioration, premature leaf fall and drying of ash trees have been observed. The deterioration affected Fraxinus excelsior and F. angustifolia on more than 200 ha, mainly on the territory of the State Hunting Enterprise Balchik, State Forest Enterprises Dobrich and General Toshevo. The results from the health status assessment carried-out in 2023 showed severely damaged ash forest belts with defoliation reaching up to 80-100% of tree crowns. Browning of leaves and petioles, and wilting of young shoots, were noticeable. Dam-age on shoots and stems of ash trees was caused by the insect pests Cicada orni, Cossus cossus, Zeuzera pyrina, Hylesinus fraxini, H. crenatus, and on leaves – by leaf-damaging and gall-forming fly Dasineura acrophila and D. fraxini. The complex of fungal species Armillaria mellea, Coriolopsis gallica, Cytospora pulchelia, Daldinia concentrica, Diplodia sp., Helicobasidium purpureum, Hysterographium fraxini, were identified on ash trees. Most of them are considered opportunistic pathogens that cause disease on trees under stress conditions. Deterioration of the health status of other major tree species was also observed. The most dangerous insect pest in oak forests – Lymantria dispar caused the defoliation of Quercus cerris belts. The endophytic fungal pathogen Biscogniauxia mediterranea was identified as a causal agent of charcoal disease on Q. rubra trees. Dutch elm disease caused by the fungus Ophiostoma novo-ulmi resulted in the wilting and death of 80-100% of Ulmus minor trees.